1997
DOI: 10.1111/j.1432-1033.1997.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subunit Truncation and the Nature of the Spacer for Single Chain Human Gonadotropins

Abstract: Three single chain gonadotropins were designed based on the three-dimensional-structure of human choriogonadotropin and structure/activity relationships of the glycoprotein hormones. In each single chain, the C-terminal end of the human choriogonadotropin /? subunit is connected via Ser-Gly repeats to the N-terminal end of the a subunit. In addition, two of the single chains have truncated subunits. The three mutants were expressed in CHO cells. In vitro binding of two of the three mutants to the human lutropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Using primers b20aarev and alphater ( Table 1) a single-chain hCG was amplified by PCR from a plasmid containing hCG mutant 1 [β-(1Ϫ111)-(Ser-Gly) 5 -A(1Ϫ92), [8]]. The resulting fragment was cloned in MB12n after digestion with BglII.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using primers b20aarev and alphater ( Table 1) a single-chain hCG was amplified by PCR from a plasmid containing hCG mutant 1 [β-(1Ϫ111)-(Ser-Gly) 5 -A(1Ϫ92), [8]]. The resulting fragment was cloned in MB12n after digestion with BglII.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this problem, we and others have produced mutants in which the coding regions of the hCG β subunit and the common A subunit are connected via peptide spacers [8] or intersubunit disulphide bonds [9]. It has been shown that these covalently linked A and β subunits of hCG are able to fold into biologically active conformations.…”
mentioning
confidence: 99%
“…The primers were chosen in such a way that the PCR fragments contained appropriate restriction sites 3 H and 5 H of the mutation, so that they could be exchanged with the native a-chain sequence in the expression vector described previously [9,14]. Mutations were confirmed using an automated sequencer (Pharmacia).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…Previously, we have shown that a truncated single-chain human choriogonadotropin is able to elicit a biological response on the human lutropin/choriogonadotropin receptor [9]. However, both its receptor-binding affinity and in vitro biological activity are reduced substantially.…”
Section: Design Of the Mini-choriogonadotropinsmentioning
confidence: 99%
See 1 more Smart Citation